Resilient Attitudes and Fear of Contagion of COVID-19 in Secondary School Students in Peru and Mexico - Huaire Inacio, Edson Jorge; Arteta Huerta, Hernán Alfonso; Llanos Miranda, Kelva Náthally; Gómez-Esquivel, Dulce Areli (Revista de Filosofía, 2022)
Resilient attitudes in times of a COVID-19 pandemic have allowed children and adolescents to develop protective factors to continue developing adequately. This is evidenced in the current study, whose objective was to analyze the association between resilient attitudes and fear of contagion by COVID-19. The sample consisted of 282 high school students from two countries, Peru and Mexico: The ages ranged between 12 to 21 years of age for students from Peru and between 12 to 22 years of age for those from Mexico. Two questionnaires were used as measurement instruments, the (1993) Wagnild and Young resilience scale, which has 25 items, and the COVID-19 fear scale (FCV-19S) created by Ahorsu, Lin, Imani, Saffari, Griffiths. and Pakpour (2020). The results show that there is an association between resilient attitudes and fear of contagion by COVID 19. However, considering the results by country, in Peruvian students there is an association between the variables, while in the Mexican sample, there is no association. Regarding the association between the dimensions of resilience and fear of contagion by COVID-19 in Peruvian students, an association was found in three factors: equanimity, perseverance, and satisfaction; while in Mexican students only the self-confidence factor is associated with fear of contagion. It is concluded that, despite the fact that the students show high levels of resilience, Mexican students have less fear of contagion than their Peruvian counterparts, for which, probably culture, the information received about the pandemic, and their self-confidence, etc., may play an important role in this difference.